OPTIMALISASI TATA KELOLA MANAJEMEN TERPADU PADA PROGRAM TRANSFORMASI WARGA SIPIL MENAJADI KOMOPONEN CADANGAN MATRA LAUT - Fizza Alimah; Wiwik Handayani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The transition of civilian identity into the national defense system through the Reserve Component (Komcad) program demands an integrated managerial system. This community service initiative aims to evaluate the effectiveness of implementing integrated management functions during the 2025 Naval Reserve Component Basic Military Training at Kodikmar. Using participatory observation and direct field involvement, the authors analyze the synchronization between Management Information Systems (MIS), Management Accounting, and Retail Management schemes in supporting educational operations. Field observations indicate that real-time information technology utilization minimizes administrative errors, while strict cost control ensures logistical budget efficiency. Furthermore, the program has proven to provide an economic stimulus for MSMEs around the training site and strengthens the institution's positive brand image through social marketing communication strategies. The success of this transformation underscores that organizational governance quality is a key factor in developing professional and accountable defense human resources.